Advance in Structural Bioinformatics - Wei, Dongqing; Xu, Qin.; Zhao, Tangzhen; Dai, Hao.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This text examines in detail mathematical and physical modeling, computational methods and systems for obtaining and analyzing biological structures, using pioneering research cases as examples. As such, it emphasizes programming and problem-solving skills. It provides information on structure bioinformatics at various levels, with individual chapters covering introductory to advanced aspects, from fundamental methods and guidelines on acquiring and analyzing genomics and proteomics sequences, the structures of protein, DNA and RNA, to the basics of physical simulations and methods for conformation searches. This book will be of immense value to researchers and students in the fields of bioinformatics, computational biology and chemistry. Dr. Dongqing Wei is a Professor at the Department of Bioinformatics and Biostatistics, College of Life Science and Biotechnology, Shanghai Jiaotong University, Shanghai, China. His research interest is in the general area of structural bioinformatics.
Introduction to Structural Bioinformatics -- Modeling and Structure Determination -- The Structure Prediction of Biological Macromolecules -- The Biological Macromolecules in Computational Biology -- The Functional Analysis of Biological Macromolecules -- The Structure-Based Drug Design.
Keywords: Bioinformatics; Molecular biology; Enzymology; Chemistry, Physical and theoretical; Bioinformatics; Computational Biology/Bioinformatics.; Molecular Medicine; Enzymology; Theoretical and Computational Chemistry